Réponses

2013-05-25T16:39:04+02:00

g(4)=-14

g(-10)=35

g(x)=ax

a=-14/4=3,5

g(x)=-3,5x

 

44

f(x)=(1+p/100)x

a)f(x)=1,13x

b) f(x)=1.38x

c) f(x)=1,69x

d)f(x)=2.03x

e)f(x)=1,005x

2)

f(x)=1-p/100)x

a) f(x)=0,66x

b) f(x)=0.28x

c)f(x)=0.46x

d)f(x)0,994)x

e)f(x)=0,01x

  • Utilisateur Brainly
2013-05-25T19:38:50+02:00

g(4)=-14

g(-10)=35

g(x)=ax

a=-14/4=3,5

g(x)=-3,5x

 

44

f(x)=(1+p/100)x

a)f(x)=1,13x

b) f(x)=1.38x

c) f(x)=1,69x

d)f(x)=2.03x

e)f(x)=1,005x

2)

f(x)=1-p/100)x

a) f(x)=0,66x

b) f(x)=0.28x

c)f(x)=0.46x

d)f(x)0,994)x

e)f(x)=0,01x

   jespere que ca ta aidé